Activities of Honey bee colonies in El-omeid, natural protectorate area, Egypt - Elbassiouny, A. M.; Mady, I. A. (2007)
To develop honey quantities produced by honey bee colonies in the Nile valley, 120 bee colonies were transported (mid-October) to El-Omeid area at El-hamam center (120 km west of Alexandria) a natural protectioraten area, rich with wild medicinal and ornamental plants and depends on the rainfall only. The blooming period started in mid - December. The experimental colonies were divided into 3 groups according to their strength and queen status [1st group(queens are less than one year old and bees covered 5 combs), 2nd group(queens are less than one year old and bees covered 3 combs) and 3rd group (queens are about two years old and bees covered 4 combs)]. It was found that colony strength (combs covered with adult worker bees) increased from 5 to 7.3 combs, from 3 to 7.1 combs and from 4 to 5.7 in the successive groups, respectively. Moreover, the brood combs, which depend on the colony strength, were also increased from 3 to 5.7, from 2 to 5.1 and from 2 to 3.4 brood combs / colony for 1st, 2nd and 3rd groups, respectively. In addition, 40 divisions of bee swarms representing the fourth group were grown up from 3.3 to 5.1 combs / colony and the brood combs increased from 2.3 to 2.8 combs / colony. The percentages of adult workers infestation by Varroa mites were decreased from 6.7 to 1.6 % in the 1st group, from 8.1 to 1.2 % in the 2nd group, from 5.1 to 2.0 % in the 3rd group and from 3.4 to 2.1% in the 4th group, at the period extended from Mid-October till the 3rd week of March. This may be due to feeding the bees on medicinal and ornamental plants (this trend was noticed in El-Arish, north Sini). The quantities of produced honey were 7.1, 6.4, 4.3 and 2.8 Kg / colony for 1st, 2nd, 3rd and 4th Sinai groups, respectively with an average of 5.15 Kg per colony.
Includes reference.
Summary in arabic.
1
Keywords: Honeybee; Honeybee -- Behavior; Honeybee -- Feeding and feeds